Antioxidant and Phytochemical analysis of selected lichen species from Mizoram, India - Lalremruata, P. C.; Lalmuanpuii, Rosie; Ralte, Vanlalhruaii; Zothanmawia; Lalthanpuii, P. B.; Lalchhandama, K.; Lalfakzuala, R. (Journal of Phytology, 2022)
Lichens are an important source of biologically active substances, primarily phenols, which are well known for their antioxidant properties. The aim of the present study was to evaluated phytochemical constituents (flavonoids and phenols), and the antioxidant activity of the methanol extract of the selected lichens species viz. Usnea baileyi, Hypotrachyna cirrhata and Lobaria pulmonaria collected from Tawi Wildlife Sanctuary, Mizoram, India. The total phenolic content and total flavonoid of the various extracts varied from 31.11 to 67.84 mg of Gallic acid equivalent per gram dry weight (GAE/g DW) and from 27.43 to 37.06 mg of Quercetin equivalent per gram dry weight (QE/g DW) respectively. DPPH free radical scavenging activity of the methanol extract of tested samples showed a concentration-dependent manner with an IC50 value ranges from 133.6 µg/ml in L. pulmonaria to 243.9 µg/ml in U. baileyi. A comparison between lichens extract and positive control (BHT) showed a strong antioxidant capacity (IC50=10.81 μg/ml) of positive control than the lichens methanolic extract. A high negative and significant negative correlation (P<0.05) was observed between total phenol content and antioxidant activity IC50 of DPPH assay. Moreover, a positively high significant correlation was also obtained between total flavonoid and phenol content (P<0.01). The present study showed that bioactive compounds present in the lichen thallus may be used as good sources of natural antioxidants and a potential candidate for curing several ailments.